Maternal body dissatisfaction in pregnancy, postpartum and early parenting: An overlooked factor implicated in maternal and childhood obesity risk. (1st April 2020) - Bergmeier, Heidi; Hill, Briony; Haycraft, Emma; Blewitt, Claire; Lim, Siew; Meyer, Caroline; Skouteris, Helen
Abstract: Background: Current evidence indicates that to prevent the intergenerational transfer of overweight and obesity from parent to child, interventions are needed across the early life stages, from preconception to early childhood. Maternal body image is an important but often overlooked factor that is potentially implicated in both short- and long-term maternal and child health outcomes, including maternal gestational weight gain, postpartum weight retention, obesity, child feeding practices and early parenting. Aim: The aim of this paper is to propose a conceptual model of the relationship between maternal body image (with a specific focus on body dissatisfaction) and maternal and child excess body weight risk across the pregnancy, postpartum and early childhood periods, as well as to highlight opportunities for intervention. Conclusion: Our conceptual model proposes factors that mediate the associations between antenatal and postpartum maternal body dissatisfaction and maternal and childhood obesity risk. Pregnancy and postpartum present key risk periods for excess weight gain/retention and body dissatisfaction. Psychosocial factors associated with maternal body dissatisfaction, including psychopathology and disordered eating behaviours, may increase maternal and child obesity risk as well as compromise the quality of mother-child interactions underpinning child development outcomes, including physical weight gain. Our conceptual model may be useful for understanding modifiable psychosocial factors for preventing the intergenerational transfer of obesity risk from mothers to their children, from as early as pregnancy, and highlights next steps for multidisciplinary research focused on combatting maternal and child obesity during critical risk periods.